Age-stratified analysis of the BMI-kidney stone relationship: findings from a national cross-sectional study - Liuliu Zhou; Wei Gu; Yufeng Jiang; Haimin Zhang (Frontiers in Medicine)
BackgroundThe association between body mass index (BMI) and kidney stone formation may vary across different age groups and follow nonlinear patterns.MethodsThis study analyzed data from NHANES 2009–2018, including 14,880 participants aged ≥20 years, to evaluate the association between BMI and the risk of kidney stones. BMI was categorized as normal weight (<25.0 kg/m2), overweight (25.0–29.9 kg/m2), and obesity (≥30.0 kg/m2). Weighted logistic regression models were employed to adjust for multiple confounders, including sex, age, race/ethnicity, education level, smoking history, alcohol consumption, coronary heart disease, diabetes mellitus, hypertension, and physical activity. Interaction effects between BMI and key variables such as sex, race/ethnicity and other factors were also analyzed. Age-stratified analyses were performed for the groups aged 20–39 years, 40–59 years, and ≥ 60 years. A restricted cubic spline model was used to explore the non-linear relationship between BMI and the risk of kidney stones.ResultsAfter adjusting for confounders, participants with a BMI ≥30 kg/m2 had a significantly higher risk of kidney stones compared to those with a BMI <25 kg/m2 (adjusted OR [aOR]: 1.86; 95% CI: 1.48–2.34; p < 0.001), with the association being most pronounced in the 40–59-year age group (aOR: 2.02; 95% CI: 1.36–3.02; p < 0.001). The interaction analysis did not reveal significant interactions between BMI and sex or other factors. Non-linear analysis indicated that the relationship between BMI and kidney stone risk differed across age groups. In the 40–59-year group, the risk of kidney stones peaked and then plateaued as BMI increased beyond a certain threshold. In the ≥60-year age group, risk initially increased with BMI but then slightly declined. This non-linear relationship suggests that the impact of BMI on kidney stone risk varies by age and should be considered in clinical strategies.ConclusionHigh BMI is significantly associated with an increased risk of kidney stones, particularly among middle-aged and older adults. The relationship between BMI and kidney stones is non-linear, highlighting the need to develop age-specific BMI management strategies to reduce the occurrence of kidney stones.